Spreadsheets with a Semantic Layer - Kohlhase, Andrea; Kohlhase, Michael (Electronic Communications of the EASST, 2013)
Spreadsheets are active documents that are heavily employed in administration, financial forecasting, education, and science because of their intuitive, flexible, and direct approach to computation. But they are also error-prone, poorly documented, often contain actual data in legacy form. Therefore, assistance for high-impact spreadsheet users is needed. To determine what kind of help could be useful, we analyze user expectations with an “Wizard-of-Oz” experiment. This shows that background knowledge is missing in spreadsheets. In the SACHS project we approach the missing background knowledge by adding a semantic layer. We illustrate spreadsheets with a semi-formal domain ontology and equip them with a semantically transparent interface that allows new forms of interaction like “semantic navigation”, “framing”, or “playing with variants”, on which a survey is given. Moreover, an integration of assessment knowledge into the SACHS approach is presented. We model it based on theory graphs and sketch a potential SACHS extension with innovative assessment interaction.